INFEKSI SOIL TRANSMITTED HELMINTHS PADA ANAK USIA SEKOLAH DASAR: PERILAKU JAJAN DAN PERILAKU HIGIENE - Sari, Octavia Permata; Susiawan, Lieza Dwianasari; Wisesa, Sindhu; Harini, Ika Murti; Setiawati, Setiawati (Mandala Of Health, 2024)
Soil Transmitted Helminths (STH) are a group of parasitic nematodes that pass through the soil in their life cycle. STH can infect the digestive system and cause harm to humans. One of the risk factors for STH is snacking behavior and poor hygiene behavior in school-aged children. This study aims to determine the relationship between snacking behavior and hygiene behavior with the incidence of STH infection in students at SDN Ciberem, Sumbang District, Banyumas Regency. This research is an analytical observational study with a cross-sectional design and was carried out using purposive sampling. The population of this study were students in grades 1-5 at SDN Ciberem with a sample size of 96 students. Data collection was carried out using questionnaires and fecal examination at the FK Unsoed Parasitology Laboratory using qualitative methods. The data obtained were analyzed using Fisher's Exact Test. In this study, it was found that 5 students (5.2%) were infected with Trichuris trichiura type STH. The Fisher's Exact test showed a significant relationship between STH infection with hand washing habits (p = 0.037), the condition of the snacks being served open (p = 0.026), and lots of flies around the snacks (p = 0.031), but there was no significant relationship with the habit of using footwear (p = 1.000), the habit of cutting nails (p = 0.256), and the frequency of snacks (p = 0.333). There is a significant relationship between the habit of washing hands, buying open snacks and snacks with lots of flies around them and the incidence of STH infection. Key words: STH, SD, snacking behavior, hygiene behavior, washing hands